Titanium dioxide nanoparticles - Biological effects - Anna Maria Świdwińska-Gajewska; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2014)
Titanium dioxide occurs as particles of various sizes. Particles of up to 100 nm, corresponding to nanoparticles, and in the size range of 0.1-3 mm are the most frequently used. Titanium dioxide in a bulk form is not classified as dangerous substance, nevertheless nanoparticles may cause adverse health effects. Inhalation exposure to nano-TiO2 causes pulmonary inflammation that may lead to fibrotic and proliferative changes in the lungs. Many studies confirm the genotoxic effect of TiO2, especially in the form of nanoparticles, on mammal and human cells. In rats exposed to TiO2-nanoparticles by inhalation the development of tumors has been observed. However, there is no evidence of additional lung cancer risk or mortality in workers exposed to TiO2 dust. There are some studies demonstrating the adverse effect of TiO2-nanoparticles on fetal development, as well as on reproduction of animals. TiO2 nanoparticles find a still wider application and thus the risk of occupational exposure to this substance increases as well. Considering such alarming data on the biological activity of TiO2 nanoparticles, more attention should be paid to occupational exposure and its health effects. Properties of the nanoparticles, due to their larger surface area and reactivity, differ significantly from the inhalable dust of TiO2, for which the hygiene standards are mandatory in Poland. Med Pr 2014;65(5):651-663